Recent climate impacts on run-of-river hydropower and electricity systems planning in Switzerland - Yann Yasser Haddad; Lukas Gudmundsson; Jonas Savelsberg; Jared B Garrison; Elena Raycheva; Tobias Wechsler; Massimiliano Zappa; Gabriela Hug; Sonia I Seneviratne (Environmental Research Letters, 2025)
The transition towards renewable energies together with climate change is rendering electricity systems more vulnerable to climate conditions and trends. This study examines the impacts of recent climate change and variability on run-of-river (RoR) hydropower production and electricity systems planning. We present an end-to-end pipeline to convert runoff and hydropower specifications into hydropower generation and subsequently integrate it into an electricity systems model. Applying this methodology to Switzerland, we provide a re-analysis of hydropower generation for each RoR power plant with capacities of 300 KW or more for the period 1991–2022. When aggregated on a national scale, our estimations match well nationally reported production and displays a climate-driven year-to-year variability. Our results show an overall tendency towards decreased RoR production in the past decades in Switzerland due to climate change (decrease in water availability). This trend was compensated at a national level with an infrastructure expansion. Based on the derived hydropower time series, we simulate the electricity system under scenarios with either no or a high renewable energy target and showcase contrasting sensitivities of electricity prices to climate variability.